Metal-mineralized collagen bidirectional gradient scaffold for large bone repair and preparation method thereof
Patent Information
- Application Number
- CN202611390470.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明旨在克服现有骨支架力学与生物活性难以兼顾、传统外密内疏结构阻碍骨长入的缺陷,提供一种双向梯度复合支架及其制备方法,反向锌合金基体提供稳定力学支撑,梯度矿化胶原强化成骨诱导,适配四肢大段承重骨缺损修复
1)力学性能优异:可降解锌合金多孔基体弹性模量与人体松质骨匹配,可有效避免应力屏蔽效应;复合支架通过界面协同承载优化应力分布,兼具强度与韧性。
Smart Images

Figure CN122998460A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, and in particular to a metal mineralized collagen bidirectional gradient scaffold for the repair of large segments of bone and its preparation method. Background Technology
[0002] Large-segment bone defects are often caused by high-energy trauma, bone tumor resection, congenital malformations, etc., exceeding the self-repair threshold of bone tissue and easily leading to secondary nonunion, chronic pain, and functional impairment, posing a challenge to clinical orthopedic treatment. Bone tissue engineering scaffolds are the core carriers for bone defect repair, and current research mainly focuses on two major directions: materials and structures.
[0003] In terms of material systems, biodegradable metal scaffolds have excellent mechanical properties and can meet the support requirements of load-bearing parts, but they lack bioactivity and have limited osteogenic induction capabilities. Mineralized collagen simulates the composition of natural bone cell extracellular matrix, has excellent biocompatibility and bone integration, but its mechanical strength is low and it cannot be used alone for the repair of load-bearing bone defects.
[0004] In terms of structural design, traditional gradient scaffolds generally adopt a biomimetic configuration with a dense outer layer and a sparse inner layer. Although they replicate the natural bone hierarchical structure in terms of morphology, the dense pores in the outer layer will hinder the migration of cells and nutrients inward, restrict the growth of new bone from the outside to the inside, and affect the bone integration efficiency. The single-pore structure is also difficult to provide a diverse microenvironment and continuous mechanical transition suitable for bone regeneration.
[0005] Therefore, there is an urgent need to develop a novel gradient bone repair scaffold that takes into account mechanical support, bioactivity, and material transport performance to meet the clinical repair needs of large-segment weight-bearing bone defects. Summary of the Invention
[0006] This invention aims to overcome the shortcomings of existing bone scaffolds, which struggle to balance mechanical and bioactivity, and the traditional dense outer and sparse inner structure that hinders bone ingrowth. It provides a bidirectional gradient composite scaffold and its preparation method, in which a reverse zinc alloy matrix provides stable mechanical support, and gradient mineralized collagen enhances osteogenic induction, making it suitable for repairing large-segment weight-bearing bone defects in the limbs.
[0007] To achieve the above objectives, the present invention provides a metal mineralized collagen bidirectional gradient scaffold for the repair of large segments of bone, comprising a biodegradable zinc alloy porous matrix and gradient mineralized collagen filling the pores inside the biodegradable zinc alloy porous matrix. The biodegradable zinc alloy porous matrix has a reverse gradient porous structure with a sparse outer layer and a dense inner layer, serving as the mechanical support phase of the scaffold; the gradient mineralized collagen has a radial mineralization gradient structure with a high outer layer and a low inner layer, serving as the bio-inducing phase of the scaffold; the biodegradable zinc alloy porous matrix and the gradient mineralized collagen are combined to form a bidirectional gradient integral structure for the repair of large bone defects.
[0008] Preferably, the biodegradable zinc alloy porous matrix is a ring-link stacked porous structure, with rings and links arranged alternately in the axial direction and composed of several layers of concentric circles in the radial direction; the radial distance between adjacent concentric circles decreases gradually from the outside to the inside.
[0009] Preferably, the material parameters of the biodegradable zinc alloy are: density 6.975 g / cm³. 3 Young's modulus 8.8 × 10 3 MPa, Poisson's ratio 0.3.
[0010] Preferably, the gradient mineralized collagen is prepared by in vitro diffusion mineralization of a composite hydrogel of type I collagen and sodium alginate; during preparation, a 1.5% type I collagen stock solution is diluted to a 1% collagen solution, and mixed with a 1% sodium alginate solution at a volume ratio of 1:1 to obtain a composite hydrogel matrix.
[0011] Preferably, the porosity of the gradient mineralized collagen gradually increases radially from the edge to the center; its radial elastic modulus gradually decreases from the outside to the inside; and the deposition of calcium and phosphorus elements gradually decreases radially from the edge to the center of the gradient mineralized collagen.
[0012] Preferably, the elastic modulus of the biodegradable zinc alloy porous matrix is 650-750 MPa, which matches the elastic modulus of human cancellous bone.
[0013] This invention also provides a method for preparing the above-mentioned metal mineralized collagen bidirectional gradient scaffold for the repair of large segments of bone, comprising the following steps: S1. Preparation of reverse gradient biodegradable zinc alloy porous matrix: A biodegradable zinc alloy porous matrix is designed with alternating stacked rings and connecting rods. The influence of ring height, connecting rod height and radial concentric circle spacing on the mechanical properties of the support is analyzed by finite element axial compression simulation. The optimal structural parameters are screened, and a reverse gradient biodegradable zinc alloy porous matrix with porosity gradually decreasing from the outside to the inside is prepared by 3D printing technology. S2. Preparation of gradient mineralized collagen raw materials: A composite hydrogel precursor was prepared using type I collagen and sodium alginate as raw materials. After cross-linking and molding, it was immersed in a biomimetic mineralization solution for time-sequential diffusion mineralization. By controlling the mineralization time, the diffusion and deposition degree of mineral ions was regulated to obtain radial gradient mineralized collagen with high edge mineralization and low center mineralization. S3. Bidirectional gradient composite molding: Gradient mineralized collagen is filled into the pores of a biodegradable zinc alloy porous matrix, and after freeze-drying, a metal mineralized collagen bidirectional gradient scaffold is obtained.
[0014] Preferably, in S1, the finite element axial compression simulation process is as follows: A three-dimensional model of a biodegradable zinc alloy porous matrix was established and tetrahedral meshes were generated. Boundary conditions were set such that the bottom surface was completely fixed and the upper pressure plate applied axial compression displacement, with the compression amount being 10% of the support height. The mechanical properties of different parameter combinations were compared using stress distribution uniformity, maximum stress value, and elastic modulus as evaluation indicators, and the optimal structure matching the mechanical properties of human cancellous bone was selected.
[0015] Preferably, in S2, the preparation method of the composite hydrogel precursor is as follows: dilute the type I collagen stock solution with acetic acid and deionized water to a mass fraction of 1%, and adjust the pH to neutral using NaOH solution; prepare a 1% sodium alginate aqueous solution, and stir at room temperature until completely dissolved and clear; mix the collagen solution and sodium alginate solution at a volume ratio of 1:1, and gently stir at 4°C for 2-4 hours until uniformly mixed; The cross-linking molding process is as follows: the composite hydrogel precursor is injected into the molding mold, a CaCl2 solution with a concentration of 20mM is added, and the cross-linking is completed by standing at room temperature for 30 minutes; after cross-linking, the gel is taken out and rinsed with deionized water 3 times, each rinsing time is 2 minutes.
[0016] Preferably, in S2, the composition of the biomimetic mineralizing solution is: an aqueous solution containing 0.1 wt% polyacrylic acid, 20 mM CaCl2, and 12 mM (NH4)2HPO4, with the pH value adjusted to 7.4 using NaOH; The process parameters for the time-series diffusion mineralization are as follows: the cross-linked hydrogel is completely immersed in the biomimetic mineralization solution, and the mineralization cycle is 0 to 6 days; the mineralization solution is replaced with fresh mineralization solution every 24 hours, and the sample is rinsed with deionized water 3 times for 2 minutes each time the solution is replaced; after the mineralization is completed, the sample is taken out and freeze-dried to obtain radial gradient mineralized collagen.
[0017] Therefore, the present invention employs the above-mentioned metal mineralized collagen bidirectional gradient scaffold for large-segment bone repair and its preparation method, which has the following beneficial effects: 1) Excellent mechanical properties: The elastic modulus of the biodegradable zinc alloy porous matrix matches that of human cancellous bone, which can effectively avoid stress shielding effect; the composite scaffold optimizes stress distribution through interface synergistic load bearing, combining strength and toughness.
[0018] 2) Biomimetic gradient structure: Gradient mineralized collagen exhibits a radial mechanical gradient that decreases from the outside to the inside, which is highly consistent with the mechanical transition characteristics of natural bone tissue.
[0019] 3) Excellent bioactivity: The reverse gradient structure with a loose outer layer and a dense inner layer has higher permeability and gentler wall shear stress, which is conducive to cell adhesion, nutrient transport and bone tissue ingrowth; gradient mineralized collagen has good biocompatibility and osteogenic induction ability, which synergistically improves the repair efficiency of large bone defects.
[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the structure of the biodegradable zinc alloy porous matrix of the present invention.
[0022] Figure 2 This is a top view of the structure of the biodegradable zinc alloy porous matrix of the present invention, which features a) a dense outer layer and a sparse inner layer with a positive gradient, and b) a sparse outer layer and a dense inner layer with a reverse gradient.
[0023] Figure 3 This invention describes the preparation process of gradient mineralized collagen.
[0024] Figure 4 The present invention includes: A) SEM pore markings of different regions of mineralized collagen after 6 days of diffusion; and B) changes in the average pore area of different regions.
[0025] Figure 5 This invention presents the elemental distribution and mineralization gradient characteristics of collagen scaffolds under different mineralization times; A) SEM morphology and EDS elemental surface scans of the edge and central regions; B) Quantitative statistics of P element content in the edge and central regions; C) Schematic diagram of radial mineralization gradient evolution.
[0026] Figure 6 The present invention describes the collagen scaffold under different mineralization times, including A) Fourier transform infrared spectra, B) X-ray diffraction patterns, and C) enzymatic hydrolysis characteristics.
[0027] Figure 7 The present invention includes: a) stress-strain curves and b) elastic modulus changes of collagen scaffolds at different mineralization times; c) stress-strain curves and d) elastic modulus of mineralized collagen in different regions after 6 days of mineralization.
[0028] Figure 8 This is a flowchart of the preparation process of the metal mineralized collagen bidirectional gradient scaffold of the present invention. A) Degradable zinc alloy porous matrix and B) Top view of gradient mineralized collagen; C) Solid view of bidirectional gradient scaffold a1) Top view a2) Front view a3) Cross-sectional view.
[0029] Figure 9 These are the a) stress-strain curves and b) elastic modulus of the three types of supports of the present invention.
[0030] Figure 10 The stress-strain curves of the externally dense and internally sparse forward support and the externally sparse and internally dense reverse biodegradable metal alloy support of the present invention, as well as the relationship curve between element loss rate and strain, are shown. Detailed Implementation
[0031] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0032] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning understood by one of ordinary skill in the art to which this invention pertains. The terms "first," "second," and similar terms used in this invention do not indicate any order, quantity, or importance, but are merely used to distinguish different components. Terms such as "comprising" or "including" mean that the element or object preceding the word encompasses the elements or objects listed following the word and their equivalents, without excluding other elements or objects. Terms such as "connected" or "linked" are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. Terms such as "upper," "lower," "left," and "right" are used only to indicate relative positional relationships; when the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0033] Example 1 This embodiment provides a metal-mineralized collagen bidirectional gradient scaffold for the repair of large bone segments, as shown in various structural views below. Figure 1 As shown, it is composed of a biodegradable zinc alloy porous matrix and gradient mineralized collagen filling its pores. The whole is cylindrical with an outer diameter of 6.0 mm and a total height of 1.5 mm.
[0034] The biodegradable zinc alloy porous matrix is a stacked ring-linkage reverse gradient porous structure. In the axial direction, two layers of rings and a middle layer of links are alternately arranged, while in the radial direction, it consists of five layers of concentric rings, each with a wall thickness of 0.2 mm. The ring height is 600 μm, and the link height is 300 μm. Along the radial direction from the outside to the inside, the spacing between adjacent concentric circles is D1=600 μm, D2=500 μm, D3=400 μm, and D4=300 μm, forming a reverse gradient structure where the porosity gradually decreases from the outside to the inside. The density of this biodegradable zinc alloy porous matrix material is 6.975 g / cm³. 3 The bulk Young's modulus is 8.8 × 10⁻⁶. 3 With a strength of MPa and a Poisson's ratio of 0.3, the overall elastic modulus of the biodegradable zinc alloy porous matrix after molding is 650-750 MPa, which matches the mechanical properties of human cancellous bone.
[0035] Gradient mineralized collagen filled the pores of a biodegradable zinc alloy porous matrix. It was prepared by time-sequential diffusion mineralization of type I collagen-sodium alginate composite hydrogel, forming a radial mineralization gradient with higher values on the outside and lower values on the inside: along the radial direction of the scaffold from the edge to the center, the deposition of calcium and phosphorus elements gradually decreased. After 6 days of mineralization, the phosphorus content in the edge region was about 4.53 wt%, and in the center region it was about 0.93 wt%. The corresponding elastic modulus decreased continuously from 1.32 MPa at the edge to 0.58 MPa at the center, and the porosity gradually increased from the edge to the center.
[0036] After composite formation, the biodegradable zinc alloy porous matrix serves as the mechanical support phase, bearing the main compressive load, while the gradient mineralized collagen acts as the biological induction phase, playing a role in stress buffering, osteogenic induction, and nutrient transport. The two form a two-way gradient synergistic system with structural and compositional gradients.
[0037] Example 2 This embodiment is used to prepare the bidirectional gradient scaffold described in Example 1, such as... Figure 8 As shown, Figure 8 Figure A in the diagram shows a reverse gradient biodegradable porous zinc alloy matrix. Figure 8 Figure B in the diagram is a top view of gradient mineralized collagen; Figure 8 Figure C in the diagram shows a bidirectional gradient scaffold, where a1, a2, and a3 are respectively a top view, a front view, and a cross-sectional view. The specific fabrication steps are as follows: S1. Preparation of a reverse gradient degradable porous zinc alloy matrix.
[0038] S11, Parametric Modeling and Structural Optimization.
[0039] A 3D parametric model of a ring-link stacked support was created using 3D modeling software. The outer diameter was set to 6.0 mm, the wall thickness to 0.2 mm, and the ring height, link height, and radial concentric circle spacing were adjusted. The model was then exported. Imported into finite element analysis software, a tetrahedral mesh with a size of 0.05 mm was created, and material properties and boundary conditions were set: the bottom surface was completely fixed, and a rigid pressure plate above applied an axial compressive displacement of 10% of the support height. The friction coefficient between the support and the pressure plate was 0.2. Stress distribution uniformity, elastic modulus, and maximum stress were used as evaluation indicators. The mechanical responses of multiple parameter combinations were compared, and the optimal structural parameters were finally selected: ring height 600 μm, link height 300 μm, and radial spacing from the outside to the inside of 600 μm, 500 μm, 400 μm, and 300 μm.
[0040] S12, 3D printed.
[0041] Selective laser melting was used to prepare a scaffold blank by printing a model based on biodegradable zinc alloy powder. The blank was then degreased, ultrasonically cleaned with anhydrous ethanol for 15 minutes, and vacuum dried to obtain a biodegradable zinc alloy porous matrix with an outer sparse and inner dense reverse gradient.
[0042] S2, Gradient mineralized adhesive raw material preparation process as follows: Figure 3 As shown.
[0043] S21, Preparation of composite hydrogel precursor solution.
[0044] Take a 1.5% (w / w) type I collagen stock solution and dilute it to a 1% (w / w) concentration with acetic acid and deionized water. Adjust the pH to neutral using 0.1 mol / L NaOH solution. Separately prepare a 1% (w / w) sodium alginate aqueous solution and stir magnetically at room temperature until completely dissolved and clear. Mix the collagen solution and sodium alginate solution at a 1:1 (v / v) ratio and gently stir at 4°C for 2-4 hours to obtain a homogeneous composite hydrogel precursor solution.
[0045] S22, cross-linking molding.
[0046] Inject the precursor solution into the molding mold, add a 20mM CaCl2 solution, and let it stand at room temperature for 30 minutes to complete crosslinking. After removing the gel, rinse it three times with deionized water for 2 minutes each time to remove residual free calcium ions.
[0047] S23, temporal diffusion mineralization.
[0048] Preparation of the biomimetic mineralization solution: Using deionized water as the solvent, add 0.1 wt% polyacrylic acid, 20 mM CaCl2, and 12 mM (NH4)2HPO4. After stirring and dissolving, adjust the pH to 7.4 with NaOH. Completely immerse the cross-linked hydrogel in the biomimetic mineralization solution and mineralize at room temperature for 6 days. Replace the mineralization solution with fresh solution every 24 hours, rinsing the sample three times with deionized water for 2 minutes each time. After mineralization, remove the sample, freeze-dry, and obtain radially graded mineralized collagen.
[0049] S3, Construction of a bidirectional gradient composite scaffold.
[0050] Based on the pore structure of a reverse gradient biodegradable zinc alloy porous matrix, gradient mineralized collagen is filled into the pores of the zinc alloy porous matrix. Specifically, the reverse gradient zinc alloy porous matrix prepared in S1 is placed in a mold, and the composite hydrogel precursor solution prepared in S2 is injected into the mold, allowing the precursor to fully penetrate into the pores of the metal scaffold. Subsequently, CaCl2 solution is added to complete cross-linking, and then it is transferred to a biomimetic mineralization solution for time-sequential diffusion mineralization. After freeze-drying, a metal mineralized collagen bidirectional gradient scaffold is obtained.
[0051] In the resulting metal mineralized collagen bidirectional gradient scaffold, the biodegradable zinc alloy porous matrix serves as the mechanical support phase, bearing the core compressive load, while the gradient mineralized collagen, as the bio-inducing phase, achieves uniform stress transfer through gradient mechanical properties. Finite element compression simulation results show that the composite scaffold, while retaining the high load-bearing capacity of the zinc alloy, optimizes stress distribution and reduces local stress concentration through interfacial synergistic load bearing, thus possessing both strength and toughness.
[0052] The gradient mineralized collagen prepared in this embodiment was characterized as follows: 1) The microstructure of graded mineralized collagen was observed using scanning electron microscopy (SEM). Lyophilized samples were cut into semi-circular slices with a diameter of 1 cm and a thickness of 1 mm, fixed to the sample stage with conductive adhesive, and coated with platinum by ion sputtering. The cross-sections and axial sections of the samples were observed at 15 kV. Figure 4 As shown in Figure B, on day 1, the pore area in the edge region is 17.967 × 10⁻⁶. -2 mm 2 It was significantly lower than the central region's 24.433 × 10⁻⁶. -2 mm 2 This indicates that mineralization preferentially initiates at the periphery of the scaffold due to higher ion accessibility. Between days 3 and 4, the pore areas of the two regions tended to converge, with a statistically significant decrease observed in the edge region; after day 4, the edge region exhibited accelerated pore closure, and on day 5, the pore area plummeted to 6.333 × 10⁻⁶. -2 mm 2 On the 6th day, it further decreased to 4.1 × 10 -2 mm 2 Conversely, the central region maintained a relatively high porosity, leading to significant differences between the periphery and the center at these two time points. From day 5 to day 6, the change in pore area was smaller at the periphery and larger at the center, indicating that mineralization at the support periphery reached saturation, while increased mineral ion diffusion in the central region led to increased mineral deposition. Figure 4 As shown in Figure A, after 6 days of ion diffusion, the porosity of the scaffold edge region (Figure b) and the central region (Figure a) are similar. This indicates that excessively long mineralization time can lead to overall densification, thereby causing the scaffold's gradient to disappear.
[0053] 2) Energy-dispersive X-ray spectroscopy (EDS) was used to analyze the elemental distribution of the mineralized samples, determining the calcium and phosphorus content in the edge and central regions. The results showed that after 6 days of mineralization, the phosphorus content in the edge region was approximately 4.53 wt%, while the phosphorus content in the central region was approximately 0.93 wt%. The phosphorus content in the edge region was approximately 4.87 times that of the central region, forming a stable radial mineralization gradient. Figure 5 As shown, Figure 5 In Figure A, a1-a3 represent the surface scan results of Ca (green) and P (red) elements in the edge region of the support after 1 day of mineralization. The results show that these two elements are highly abundant and uniformly distributed, while the element signal intensity in the central region, represented by b1-b3, is significantly lower than that at the edge, showing only a sparse distribution, further confirming the edge-preferential nucleation characteristic in the early stage of mineralization; after 6 days of mineralization, Figure 5 In Figure A, the Ca and P element signals in the edge regions represented by c1-c3 are further enhanced and more uniformly distributed, while the element signals in the central region are significantly improved compared to day 1. Figure 5A(d1-d3)), mineralizing elements achieve effective penetration and deposition from the edge to the center. Quantitative statistical results of P element content show ( Figure 5 (Figure B in the diagram) Throughout the mineralization cycle, the phosphorus (P) content in the edge region of the support was consistently significantly higher than that in the central region, exhibiting a stable mineralization gradient. After one day of mineralization, the P content in the edge region was 0.89 wt%, while that in the central region was only 0.25 wt%, with the edge content being approximately 3.56 times that of the central region. As the mineralization time increased, the P content in both groups continued to rise. After six days, the P content in the edge region reached 4.53 wt%, an increase of approximately 4.09 times compared to one day, while the P content in the central region was 0.93 wt%, an increase of approximately 2.72 times compared to one day. Figure 5 As shown in Figure C, during the mineralization process of the scaffold from day 1 to day 6, the mineral content forms a gradient with higher content on the outside and lower content on the inside.
[0054] 3) The chemical structure of the sample was analyzed using Fourier transform infrared spectroscopy (FTIR). The potassium bromide pellet method was employed, with the sample and KBr mixed at a mass ratio of 1:100 and pelleted. The wavenumber range was 400-4000 cm⁻¹. -1 The number of scans was 32, and the resolution was 4cm. -1 The result is as follows Figure 6 As shown in Figure A, with the extension of mineralization time, at 1030 cm... -1 600cm -1 560cm -1 The presence of characteristic absorption peaks of hydroxyapatite confirms that the mineralization product is hydroxyapatite.
[0055] 4) The crystal structure of the mineralized sample was analyzed using X-ray diffraction (XRD). The testing conditions were 45 kV, 40 mA, 2θ scanning angle range of 5°–80°, and scanning speed of 5° / min. The results are as follows: Figure 6 As shown in Figure B, a weak characteristic diffraction peak of hydroxyapatite appeared after 1 day of mineralization. As the mineralization time increased, the intensity of the hydroxyapatite diffraction peak at 2θ=25.9° and 31.9° continued to increase, indicating that the crystal gradually grew and matured.
[0056] 5) The biodegradability of the samples was evaluated using an enzyme degradation rate test. Each group of samples was immersed in PBS solution containing 0.25% trypsin and enzymatically digested for 24 hours in a 37°C water bath. Figure 6Figure C shows the mass loss rate of collagen scaffolds after 24 hours of trypsin degradation at different mineralization times. The degradation rate of pure collagen scaffolds with mineral ion diffusion at day 0 is as high as 89%, gradually decreasing with increasing mineralization time, dropping to 43.6% by day 6. Although pure collagen scaffolds possess natural cell affinity, their excessively rapid degradation rate is difficult to match the bone defect repair cycle, and early structural collapse can lead to instability of the cellular microenvironment. As mineralization progresses, minerals are deposited on collagen fibers, preventing the collagen fibers from being destroyed by the degradation solution, thus reducing the degradation rate, but still exhibiting good biodegradability.
[0057] 6) Uniaxial compression tests were conducted using an electromagnetic mechanical testing system. The samples were cut into standard disc-shaped compression specimens with a diameter of 1 cm and a height of approximately 0.5 mm, and compressed at a rate of 5% per second until failure. The results showed that at 0 days, the stress of the support at 80% strain was approximately 1.0 MPa, while at 6 days, the corresponding stress increased to over 1.5 MPa. Figure 7 (Figure a) After 6 days of mineralization, the overall elastic modulus of the support was approximately 1.67 MPa. Figure 7 Figure b in the diagram). Stress-strain curves were obtained by testing different areas of the support 6 days after mineralization. Figure 7 Figure c shows that, under the same strain, the stress level in the edge region (region C) is significantly higher than that in the middle (region B) and the center region (region C). The stress in the center region is the lowest, exhibiting a clear mechanical gradient. The elastic modulus of the edge region is approximately 1.32 MPa, while that of the center region is approximately 0.58 MPa, with the edge being about 2.28 times that of the center, showing a radial mechanical gradient with higher stress at the edge and lower stress at the center. Figure 7 (Figure d in the diagram).
[0058] Comparative Example 1 The difference between this comparative example and Example 2 is that the biodegradable zinc alloy porous matrix adopts a positive gradient pore structure with a denser outer layer and a sparser inner layer. The radial concentric circle spacings from the outside to the inside are: D1=300μm, D2=400μm, D3=500μm, and D4=600μm, respectively. The structure is as follows: Figure 2 As shown, Figure 2 Figure a shows a top view of the structure of a biodegradable porous zinc alloy matrix with a positive gradient of dense outer layer and sparse inner layer. Figure 2 Figure b in the figure is a top view of the structure of the biodegradable zinc alloy porous matrix with a reverse gradient of sparse outer layer and dense inner layer. The remaining preparation steps and parameters are the same as in Example 2. This comparative example only prepared a biodegradable zinc alloy porous matrix.
[0059] Comparative Example 2 The difference between this comparative example and Example 2 is that it does not contain a gradient mineralized collagen phase, but only uses a biodegradable zinc alloy porous matrix as a scaffold. The remaining preparation steps and parameters are the same as in Example 2.
[0060] Comparative Example 3 The difference between this comparative example and Example 2 is that it does not contain a biodegradable zinc alloy porous matrix, but only uses gradient mineralized collagen as a scaffold. The remaining preparation steps and parameters are the same as in Example 2.
[0061] The test results for the stents prepared in Example 2 and the comparative example are as follows: After axial compression testing, such as Figure 9 As shown, combined with Figure 9 As shown in Figures a and b, the elastic modulus of the bidirectional gradient scaffold in Example 2 is approximately 680.9 MPa, which highly matches the mechanical properties of human cancellous bone. Compared to Comparative Example 2, its local maximum stress is reduced by about 8%, and the stress distribution is more uniform, combining high strength with stress buffering toughness. The elastic modulus of Comparative Example 3 is only 1.67 MPa, which cannot meet the mechanical requirements of the load-bearing parts.
[0062] CFD simulation tests showed that, at an inlet flow velocity of 0.1 mm / s, the permeability of the bidirectional gradient stent in Example 2 reached 2.16 × 10⁻⁶. - 8 m 2 Compared to Comparative Example 1, it is about 70% higher; the average wall shear stress is 1.915 mPa, which is significantly lower than 2.673 mPa in Comparative Example 1. The fluid environment is milder and more conducive to cell adhesion, nutrient transport and metabolic waste removal.
[0063] Stress-induced corrosion coupled simulation tests were conducted, and the results at 10% compressive strain are as follows: Figure 10 As shown, the residual stress of the bidirectional gradient scaffold in Example 2 was maintained at 2.3~2.9MPa, which was significantly higher than that of Comparative Example 1 (1.7~2.4MPa). It exhibited a stable failure mode of preferential corrosion on the outer side and continuous load-bearing on the inner side, with better long-term mechanical support capacity, which can better match the mechanical requirements of the bone repair cycle.
[0064] Therefore, this invention employs the aforementioned metal mineralized collagen bidirectional gradient scaffold and its preparation method for repairing large bone segments. The elastic modulus of the zinc alloy matrix, with its outer sparse and inner dense structure, matches that of human cancellous bone, avoiding stress shielding, resulting in higher fluid permeability and milder shear stress on the pore walls, which facilitates the inward transport of cells and nutrients. The biomimetic extracellular matrix of mineralized collagen with an outer high and inner low gradient enhances osteogenic induction and angiogenesis capabilities. Stress corrosion simulation confirms that the inner side of the scaffold can sustain load-bearing capacity, resulting in stronger long-term mechanical stability. The combination of these two components achieves stress buffering and synergistic load-bearing, balancing mechanical strength and bioactivity, making it suitable for repairing large bone defects in weight-bearing areas of the limbs.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A metal-mineralized collagen bidirectional gradient scaffold for repairing large segments of bone, characterized in that, Includes a biodegradable zinc alloy porous matrix and gradient mineralized collagen filling the pores inside the biodegradable zinc alloy porous matrix; The biodegradable zinc alloy porous matrix has a reverse gradient porous structure with a sparse outer layer and a dense inner layer, serving as the mechanical support phase of the scaffold; the gradient mineralized collagen has a radial mineralization gradient structure with a high outer layer and a low inner layer, serving as the bio-inducing phase of the scaffold; the biodegradable zinc alloy porous matrix and the gradient mineralized collagen are combined to form a bidirectional gradient integral structure for the repair of large bone defects.
2. The metal mineralized collagen bidirectional gradient scaffold for large-segment bone repair according to claim 1, characterized in that, The biodegradable zinc alloy porous matrix is a ring-link stacked porous structure, with rings and links arranged alternately in the axial direction and composed of several layers of concentric circles in the radial direction; the radial distance between adjacent concentric circles decreases gradually from the outside to the inside.
3. The metal mineralized collagen bidirectional gradient scaffold for large-segment bone repair according to claim 1, characterized in that, The material parameters of the biodegradable zinc alloy are: density 6.975 g / cm³. 3 Young's modulus 8.8 × 10 3 MPa, Poisson's ratio 0.
3.
4. The metal mineralized collagen bidirectional gradient scaffold for large-segment bone repair according to claim 1, characterized in that, The gradient mineralized collagen is prepared by in vitro diffusion mineralization of a composite hydrogel of type I collagen and sodium alginate. During preparation, a 1.5% type I collagen stock solution is diluted to a 1% collagen solution and mixed with a 1% sodium alginate solution at a volume ratio of 1:1 to obtain the composite hydrogel matrix.
5. The metal mineralized collagen bidirectional gradient scaffold for large-segment bone repair according to claim 4, characterized in that, The porosity of the gradient mineralized collagen gradually increases radially from the edge to the center; its radial elastic modulus decreases gradually from the outside to the inside; and the deposition of calcium and phosphorus elements gradually decreases radially from the edge to the center of the gradient mineralized collagen.
6. The metal mineralized collagen bidirectional gradient scaffold for large-segment bone repair according to claim 1, characterized in that, The elastic modulus of the biodegradable zinc alloy porous matrix is 650-750 MPa, which matches the elastic modulus of human cancellous bone.
7. A method for preparing a metal-mineralized collagen bidirectional gradient scaffold for large-segment bone repair as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of reverse gradient biodegradable zinc alloy porous matrix: A biodegradable zinc alloy porous matrix is designed with alternating stacked rings and connecting rods. The influence of ring height, connecting rod height and radial concentric circle spacing on the mechanical properties of the support is analyzed by finite element axial compression simulation. The optimal structural parameters are screened, and a reverse gradient biodegradable zinc alloy porous matrix with porosity gradually decreasing from the outside to the inside is prepared by 3D printing technology. S2. Preparation of gradient mineralized collagen raw materials: A composite hydrogel precursor is prepared using type I collagen and sodium alginate as raw materials. After cross-linking and molding, it is immersed in a biomimetic mineralization solution for time-sequential diffusion mineralization. By controlling the mineralization time, the diffusion and deposition degree of mineral ions is regulated to obtain radial gradient mineralized collagen with high edge mineralization and low center mineralization. S3. Bidirectional gradient composite molding: Gradient mineralized collagen is filled into the pores of a biodegradable zinc alloy porous matrix, and after freeze-drying, a metal mineralized collagen bidirectional gradient scaffold is obtained.
8. The preparation method according to claim 7, characterized in that, In S1, the process of the finite element axial compression simulation is as follows: A three-dimensional model of a biodegradable porous zinc alloy matrix was established and a tetrahedral mesh was generated. Boundary conditions were set, with the bottom surface completely fixed and the upper pressure plate applying axial compressive displacement, the compression amount being 10% of the support height. Using stress distribution uniformity, maximum stress value, and elastic modulus as evaluation indicators, the mechanical properties of different parameter combinations were compared, and the optimal structure matching the mechanical properties of human cancellous bone was selected.
9. The preparation method according to claim 7, characterized in that, In S2, the preparation method of the composite hydrogel precursor is as follows: dilute the type I collagen stock solution with acetic acid and deionized water to a mass fraction of 1%, and adjust the pH to neutral using NaOH solution; prepare a 1% sodium alginate aqueous solution and stir at room temperature until completely dissolved and clear; mix the collagen solution and sodium alginate solution at a volume ratio of 1:1 and gently stir at 4°C for 2-4 hours until uniformly mixed; The cross-linking molding process is as follows: the composite hydrogel precursor is injected into the molding mold, a CaCl2 solution with a concentration of 20mM is added, and the cross-linking is completed by standing at room temperature for 30 minutes. After cross-linking, the gel was removed and rinsed three times with deionized water for 2 minutes each time.
10. The preparation method according to claim 7, characterized in that, In S2, the composition of the biomimetic mineralizing solution is: an aqueous solution containing 0.1 wt% polyacrylic acid, 20 mM CaCl2, and 12 mM (NH4)2HPO4, with the pH value adjusted to 7.4 using NaOH; The process parameters for the time-series diffusion mineralization are as follows: the cross-linked hydrogel is completely immersed in the biomimetic mineralization solution, and the mineralization cycle is 0 to 6 days; the mineralization solution is replaced with fresh mineralization solution every 24 hours, and the sample is rinsed with deionized water 3 times for 2 minutes each time the solution is replaced; after the mineralization is completed, the sample is taken out and freeze-dried to obtain radial gradient mineralized collagen.
